Characterization of green-synthesized zinc oxide nanoparticles and its influence on post-harvest shelf-life of garlic against black mold disease caused by Aspergillus niger - Kumawat, Govind; Rajpurohit, Deepak; Vyas, Divya; Bhojiya, Ali Asger; Upadhyay, Sudhir Kumar; Jain, Devendra (Frontiers in Microbiology, 2025)
Garlic is an important spice crop used for flavoring food and has a long history of use in traditional medicine. However, black mold is a common fungal disease affecting garlic, which was caused by an Aspergillus infection. This disease significantly impacts both the production and quality of garlic. Therefore, this study aimed to evaluate the antifungal activity of novel green-synthesized zinc oxide nanoparticles (ZnO-NPs) against black mold diseases in garlic. An environmentally friendly green synthesis technique was used to produce ZnO-NPs using zinc-tolerant bacteria Serratia sp. (ZTB24). In the present study the experimental analysis viz. UV-Vis spectroscopy at 380 nm, transmission electron microscopy (TEM), dynamic light scattering (DLS), and zeta potential confirmed the successful biosynthesis of green ZnO-NPs from Serratia sp. The poisoned food technique and spore germination test revealed the antifungal activities of ZnO-NPs against A. niger under in vitro conditions. The presence of disease-causing A. niger fungus was confirmed through its isolation from infected garlic bulbs, and it was further identified at the molecular level using inter-transcribed sequence (ITS) rDNA sequencing. ZnO-NPs reduced the mycelial growth up to 90% and the 73% spore germination at 250 μg ml−1 concentration of ZnO-NPs. The ZnO-NPs were further used in vivo at different concentrations (50, 100, 250, and 500 ppm) in the post-harvest treatment of garlic. The percentage of disease severity was assessed after 7 and 14 days, and the application of 500 ppm of ZnO-NPs exhibited 0% disease severity in the pre-inoculation method, while disease severity of black mold disease in garlic plant was recorded at 1.10% after 7 days and 0.90% after 14 days in the post-inoculation method, compared to the control group. Hence, the antifungal activity of ZnO-NPs synthesized using the green technique paves the way for the development of natural fungicides, offering a sustainable and renewable alternative to traditional chemical control methods.